On FPGA Implementation of a Continuous-Discrete Time Observer for Sensorless Induction Machine using Simulink HDL Coder - Besbes, Moez; Hadj, Salim; M’Sahli, Faouzi; Farza, Monther (International journal of advanced computer science & applications, 2017)
This paper deals with the design of a continuousdiscrete time high gain observer (CDHGO) for sensorless control of an induction machine (IM). Only two weakly sampled stator current measurements are used to achieve a real-time estimation of the rotor flux, the mechanical speed and the load torque. The feasibility of implementing our algorithm on the FPGA target is discussed in term of the best word format choice for internal variables and in term of making up for problems attached with complex bloc diagram VHDL conversion. Before an eventual implementation on the Virtex FPGA board, a validation of the proposed observer is performed through the ModelSim software where we show that the waveforms of estimates bring closer the true ones.